Analysing the Mediating Role of Self-Control and Mental Resilience on the Relationship Between Internet Addiction and Academic Procrastination - Li, Cheng; Lee, Say Wah (Journal of Ecohumanism, 2024)
The current study focuses on investigating the role of self-control and mental resilience of Chinese college students in mediating their internet addiction and procrastination on academic tasks. A cross-sectional quantitative research design has been adopted in the study with a sample of 480 first year college students from China. Standardized tools were used to assess internet addiction, academic procrastination, and mental resilience; self-control was assessed through a self-constructed scale. Quantitative data obtained on the four scales was analyzed through SPSS using descriptive and inferential statistics. Findings of the study reveal that male college students in China are more addicted to the internet and also procrastinate more compared to their female counterparts. In addition, the findings further suggest that there exists a positive relationship between internet addiction and academic procrastination, as internet addiction is the reason for procrastination among Chinese first year college students. These findings suggest that male college students in China are more negatively affected by internet use and addiction and need intervention, particularly focusing on improving their self-control and mental resilience. To improve the depth and applicability of findings, the study has emphasized the adoption of random sampling, a larger and diverse sample, and a mixed methods design.